2019
DOI: 10.1503/cjs.016817
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of postoperative delirium in the older acute care surgery population: a prospective study

Abstract: Background: Among older inpatients, the highest incidence of delirium is within the surgical population. Limited data are available regarding postoperative delirium risk in the acute care surgical population. The purpose of our study was to establish the incidence of and risk factors for delirium in an older acute care surgery population. Methods: Patients aged 65 years or more who had undergone acute care surgery between April 2014 and September 2015 at 2 university-affiliated hospitals in Alberta were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 35 publications
4
26
0
1
Order By: Relevance
“…The possible explanation for the high incidence of emergence delirium in our study might be due to inadequate preoperative optimization and reassurance of the patient, inadequate postoperative pain management, and could be due to clinical set-up differences. 22 …”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation for the high incidence of emergence delirium in our study might be due to inadequate preoperative optimization and reassurance of the patient, inadequate postoperative pain management, and could be due to clinical set-up differences. 22 …”
Section: Discussionmentioning
confidence: 99%
“…The length of hospital stays among patients with delirium was four days longer on average, and ICU stay lengths 24 hours longer, than for patients without delirium. Other studies on postoperative delirium have shown that the average length of stay for spine surgery patients was three days or longer [6,8,10], the average for hip surgery patients was two days or longer [9], the average for cardiac surgery patients was four days or longer [12], the average for acute care surgery patients was seven days or longer [4], and the average for surgical trauma ICU and major surgery patients was four days or longer [21,22]. The length of hospital stays tends to increase with post-operative delirium status.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of delirium is particularly high in elderly patients. For persons over 65 years of age, prevalence is above 30.0%, whilst for persons over 80 years of age, it ranges from 33.5% to 50.0% [3,4,5,6,7,8,9,10,11,12]. More than 80.0% of delirium cases occur one-three days post-surgery and are temporary [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive surgery has been shown to reduce postoperative pain, and the stress and inflammatory responses. However, current clinical evidence regarding delirium is conflicting, with some observational studies reporting lower risk of delirium with minimally invasive surgery 101,102 and others reporting no difference 103 (Table 1). More robust clinical evidence is needed.…”
Section: Surgical Traumamentioning
confidence: 99%